1996
DOI: 10.1017/s0268416000003489
|View full text |Cite
|
Sign up to set email alerts
|

Transition into widowhood: a life-course perspective on the household position of Icelandic widows at the beginning of the twentieth century

Abstract: Nous avons analysé la place des veuves âgées de 50 ans et plus dans les ménages ainsi que leurs occupations socio-professionnelles à partir du recensement islandais de 1901. Nous avons également utilisé les données longitudinales pour examiner la relation pouvant exister entre position dans le ménage (et migration) et temps ecoulé depuis le début du veuvage. Pour la plupart des Islandaises nées à la fin du XIXe siècle, perdre son mari signifiait moindres ressources. Cependant les moyens de subsistance comme la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Earlier research has shown that widows generally tended to migrate more often than widowers in pre-industrial and industrializing societies (Dribe et al, 2007;Gunnlaugsson & Gardarsdóttir, 1996;Van Poppel, 1995). The main explanation for widows' higher propensity to migrate is that, predominantly, widows from rural areas expected to find increased financial and social support in towns (Gunnlaugsson & Gardarsdóttir, 1996). In urban areas, widows generally had a higher chance of remaining in an independent economic position since urban labour markets offered more work opportunities than rural areas for adult women.…”
Section: Concluding Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Earlier research has shown that widows generally tended to migrate more often than widowers in pre-industrial and industrializing societies (Dribe et al, 2007;Gunnlaugsson & Gardarsdóttir, 1996;Van Poppel, 1995). The main explanation for widows' higher propensity to migrate is that, predominantly, widows from rural areas expected to find increased financial and social support in towns (Gunnlaugsson & Gardarsdóttir, 1996). In urban areas, widows generally had a higher chance of remaining in an independent economic position since urban labour markets offered more work opportunities than rural areas for adult women.…”
Section: Concluding Discussionmentioning
confidence: 98%
“…Migration can therefore be regarded as a short-term adaptation to a family crisis (Kok, 2004). Earlier research has shown that widows generally tended to migrate more often than widowers in pre-industrial and industrializing societies (Dribe et al, 2007;Gunnlaugsson & Gardarsdóttir, 1996;Van Poppel, 1995). The main explanation for widows' higher propensity to migrate is that, predominantly, widows from rural areas expected to find increased financial and social support in towns (Gunnlaugsson & Gardarsdóttir, 1996).…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Africa, more victims of widowhood exist among young women and child mothers due probably to war, ignorance, disease, or poverty. Although much of research on widows has to a large extent been dealing with widows' living conditions and strategies after losing the spouse (Bloom, 1991;Gunnlaugsson & Gardarsdottir, 1996;Johansen, 2004;Kertzer & Laslett, 1995;Moring, 2002;Wall, 2002), comprehensive research into the dimensions of widowhood practices that expose African widows to diverse criminal acts remains intensely inadequate. It is against this background that this article committed itself to filling a gap in knowledge by providing answers, using the experiences of the Ogu people of Nigeria, to the following questions: (a) What are the different widowhood practices among the Ogu women in Lagos, Nigeria?…”
Section: Introductionmentioning
confidence: 99%